Effects of hospital consolidation in Croatia assessed by safety attitudes questionnaire 2006 short form - Bulajić, Maša (Array, 2020)
On several occasions hospitals in Croatia have been a subject to consolidation. The purpose of the consolidations was savings gained by merging some of the services, especially in the hospitals which are geographically close to each other. The available published research results have shown that the smallest hospitals in Croatia achieve highest results for safety measured by the Safety Attitudes Questionnaire 2006 Short Form (SAQ). Further investigation and management of the SAQ data obtained in 2016 has proven that the analyzed independent hospitals with up to 500 beds, compared to the consolidated hospitals, achieve significantly better results with regard to Working Conditions, Management’s Attitude, Job Satisfaction and overall SAQ results. In terms of expenditures expressed as the index change of expenditures from year 2006 (2006 having an index of 100), no significant differences were found. However, the highest rise in the expenditures is found for consolidated hospitals with >500 beds, while the hospitals with <500 beds, either consolidated or not, show the same trend in the change of expenditures during the period 2006-2015. These findings should be considered when deciding upon hospitals consolidation in Croatia.